PENGARUH KOMPENSASI, JENJANG KARIR, DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN GEN Z KOTA TANGERANG DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI - Handayani; Toni Yoyo (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study is motivated by the frequent job-hopping behavior of Generation Z. Several surveys indicate that Gen Z tends to change jobs due to salary, opportunities for growth, and work environment. The aim of this research is to analyze the influence of compensation, career advancement, and work environment on the loyalty of Generation Z employees in Tangerang City, with job satisfaction as a mediating variable. This research employs a quantitative approach using the Structural Equation Modeling (SEM) method. The sample consists of 187 respondents aged 15–27 years who work across various industry sectors in Tangerang City and were selected using purposive sampling. The results show that each independent variablecompensation, career advancement, and work environment has a significant effect on both loyalty and job satisfaction. Job satisfaction also has a significant influence on employee loyalty. However, job satisfaction does not mediate the influence of compensation, career advancement, and work environment on loyalty. This study highlights the importance of improving compensation packages, providing clear career paths, and fostering a supportive work environment to enhance the loyalty of Generation Z employees in Tangerang City. Future research is expected to explore other variables not measured in this study and to select respondents with experience in specific industry backgrounds.